TiNb 합금의 양극산화법에 의한 나노튜브 생성거동 - 정은혜; Eun Hye Jung; 정봉용; Bong Yong Jeong (대한금속·재료학회지, 51(11), 2013)
Titanium and titanium alloys have been used extensively as bone-implant materials due to their high strength-to-weight ratio, good biocompatibility and excellent corrosion resistance. In this work, we investigated the surface characteristics of nanotubes formed on Ti25Nb alloys in a 0.1M NaF aqueous electrolyte containing HF using electrochemical methods. The constant voltages were widely applied to a range from 20 to 80 V. As a result, the oxide layers formed with nanotube structures in which the nanotubes increased in a linear diameter and length. The TiNb nanotube morphology was strongly influenced by the fluoride concentration, applied potential and reaction time.